Kajian Semiotika Ilustrasi Digital Karya Agung Budi Santoso (Pendekatan Semiotika Roland Barthes) - Alfa Risi; Zulkifli Zulkifli (MAVIS : Jurnal Desain Komunikasi Visual, 2022)
Agung Budi Santoso is a profesional illustrator whose work often intersects in various scopes of the creative industry in Indonesia and abroard, especially in music. The illustrative approach he uses in his works often refers to the surrealist style thus causing confusion for some people in translating the meanings of the illustrations. This study aims to find out how to understand the message conveyed in the illustrations. The method used is descriptive qualitative method, using the application of Roland Barthes’ semiotic theory through the meaning of the signifier and the signified to determine the meaning of the relation of denotative, connotative and ideological signs contained in the illustrations. The results of this study explain that presence of surrealist visualization in Agung Budi Santoso’s illustrations is often influenced by segmented references to pop culture and music itself, so that this often causes misinterpretations in his works.